The Effectiveness of Administrative Remedies as a Prerequisite for Filing a Lawsuit in the Administrative Court (PTUN) - Rafli Ramdani; Rihan Rizky; Gia Anggiani; Jasmine Az-zahra; Zakiyah Zakiyah; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effectiveness of administrative remedies as a prerequisite for filing lawsuits in the State Administrative Court (PTUN), as regulated under Law Number 30 of 2014 concerning Government Administration, Law Number 5 of 1986 concerning the State Administrative Court as amended by Law Number 9 of 2004 and Law Number 51 of 2009, as well as Supreme Court Regulation Number 6 of 2018. This research employs a normative juridical method using statutory and conceptual approaches, supported by primary and secondary legal materials. The findings indicate that normatively, administrative remedies aim to promote efficiency in dispute resolution, provide opportunities for internal correction, and reduce the caseload of the PTUN, while also functioning as a prerequisite (voorvraag) for litigation. However, in practice, their effectiveness remains limited as they are often treated as procedural formalities, influenced by limited independence, weak transparency and accountability, and low public legal awareness. Comparative analysis with civil law and common law systems shows the need to balance legal certainty and substantive justice. Strengthening regulations, institutions, and legal awareness is essential to enhance their effectiveness as legal protection.